Attacking HIV-1 RNA versus DNA by sequence-specific approaches: RNAi versus CRISPR-Cas. (19th October 2016) - Herrera-Carrillo, Elena; Berkhout, Ben
Abstract : Human immunodeficiency virus type 1 (HIV-1) infection can be effectively controlled by potent antiviral drugs, but this never results in a cure. The patient should therefore take these drugs for the rest of his/her life, which can cause drug-resistance and adverse effects. Therefore, more durable therapeutic strategies should be considered, such as a stable gene therapy to protect the target T cells against HIV-1 infection. The development of potent therapeutic regimens based on the RNA interference (RNAi) and clustered regularly interspaced short palindromic repeats (CRISPR-Cas) mechanisms will be described, which can be delivered by lentiviral vectors. These mechanisms attack different forms of the viral genome, the RNA and DNA, respectively, but both mechanisms act in a strictly sequence-specific manner. Early RNAi experiments demonstrated profound virus inhibition, but also indicated that viral escape is possible. Such therapy failure can be prevented by the design of a combinatorial RNAi attack on the virus and this gene therapy is currently being tested in a preclinical humanized mouse model. Recent CRISPR-Cas studies also document robust virus inhibition, but suggest a novel viral escape route that is induced by the cellular nonhomologous end joining DNA repair pathway, which is activated by CRISPR-Cas-induced DNA breaks. We will compare these two approaches for durable HIV-1 suppression and discuss the respective advantages and disadvantages. The potential for future clinical applications will be described.